Analisis Risiko Kecelakaan Kerja Menggunakan Metode Analisis SWIFT Pada Pekerjaan Fondasi Bored Pile - Arifatussaadah, Nenden; Rahayu, Sri; Agustian, Kusmira (Akademi Komunitas Negeri Aceh Barat, 2024)
AbstractThe Occupational Health and Safety Management System (OHSMS) aims to create a health and safety management system in the workplace that considers aspects of labour, conditions, management, and the work environment. However, there are some companies that pay less attention to the implementation of SMK3. This research focuses on the risk analysis of occupational accidents in bored pile foundation work in the construction project of the Mother and Child Services Centre of Dr. Hasan Sadikin Hospital Bandung using the Structured What If Technique (SWIFT) analysis method. SWIFT analysis is a method of identifying potential hazards using a questioning approach with the keyword